ANALYSIS OF FINE MOTOR CONTROL IN INSTITUTIONALIZED SHELTERED CHILDREN AND ADOLESCENTS THROUGH PERFORMANCE IN COMPUTER SOFTWARE - André Wesley de Araujo; Rafaela Villa Almeida; Tania Brusque Crocetta; Carlos Bandeira de Mello Monteiro; Deborah Cristina Gonçalves Luiz Fernani; Maria Tereza Artero Prado Dantas (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To analyze the psychomotor development and the fine motor control of institutionalized and non-institutionalized sheltered children and adolescents. Methods: A cross-sectional study in which 54 subjects participated and were divided into two groups: 27 institutionalized sheltered children and adolescents (SG) and 27 non-institutionalized sheltered children and adolescents (CG). The psychomotor battery and the Learning and Motor Control software were used to evaluate development and motor control. The analysis of variance was performed for both groups with repetitive measurements for the last factor. Results: The SG presented a total development score inferior to the CG, with differences in tonicity (p=0.041) and body awareness (p=0.039). The longest distance was performed on Task 1 (M=983.9 pixels; diagonal line; distance of 930.053 pixels), with no difference between the groups (p=0.64). Furthermore, the SG presented a greater average time in Task 1 (M=16.12 seconds) when compared with Tasks 2 (M=11.6 seconds; horizontal line; distance of 750 pixels) and 3 (M=10.6; vertical line; distance of 550 pixels), but only marginally different between Tasks 2 and 3 (p=0.055). Regarding the number of correct answers, the CG scored more (M=6.1) when compared with SG (M=4.6), with p<0.05. Conclusions: The institutionalized individuals showed a psychomotor development inferior to the CG. Furthermore, they presented impairment in fine motor control, covering a larger distance on the task that required the diagonal movement, longer execution time, less correct answers, and more errors.